Influence of emotional intelligence on resistance to change among employees at KPJ Kajang specialist Hospital / Presantia Anak Bujang, Nurul Hanina Mohd Zulkarnain and Sallehatul Asfiah Mohamad Salleh - Bujang, Presantia; Mohd Zulkarnain, Nurul Hanina; Mohamad Salleh, Sallehatul Asfiah (Arshad Ayub Graduate Business School, 2018)
Resistance to change has been identified as an organizational challenge for decades. Previous studies of resistance to change mostly take an organizational perspective as opposed to an individual perspective. Basically, change triggers strong emotions, which may promote tunnel vision, narrowing our productive choices. Therefore, Emotional Intelligence (EI) is essential to employees especially frontline staffs to cope with change, such as organizational restructuring, new technologies, automation, mergers and acquisitions, globalization, and new sources of competition. Hence, the purpose of this study was to examine the influence of emotional intelligence on resistance to change among employees at KPJ Kajang Specialist Hospital. This study is based on data obtained from primary data that were collected from 120 respondents (who work as frontline staffs) at KPJ Kajang Specialist Hospital. The results confirmed that there is a relationship between emotional intelligence dimensions (emotional awareness, emotional facilitation, emotional knowledge and emotional regulation) and resistance to change. However, the results also found that three emotional intelligence dimensions (emotional awareness, emotional facilitation, and emotional knowledge) have negative relationship with resistance to change. The practical implications of these findings were discussed. The study also gained few implications both in theoretical and practical which is the promotion of Emotional Intelligence (EI) among frontline staff really essential in order to be sustain in the healthcare industry. Hence, KPJ Kajang Specialist Hospital are recommended to do collaboration with other universities and colleges that are equipped with new technologies in healthcare, facilitating participation and involvement, introducing open communication channels within the organization, improving mobile information system, and offering education and training to frontline staff, supervisor and co-worker support. Finally, limitation of study was also identified after the research is done. There are suggestions for future research to be conducted for better understanding in future.